Hypospadie: Erkenntnisse und Herausforderungen = Hypospadias : insights and challenges - Rübben, Iris; Stein, Raimund (Der Urologe, 2017)
Disorders of the ventral tubularization of the urethra, such as the hypospadias, are among the second most frequent congenital childhood malformations. An increasing incidence has been observed suggesting a doubling in the US, which could not be documented for the European area. The underlying causes of this congenital defect remain unidentified. Genetic risk constellations or environmental influences, in particular by so-called endocrine disrupting chemicals (EDCs), are discussed as triggering factors. Boys after in vitro fertilization are more likely to have hypospadias than in nonreproductive-assisted pregnancies. Animal models (especially mice) elicited causal relationships between prenatal hormonal exposure (estrogens, progesterone) and antiandrogens such as flutamide, finasteride, antiandrogenic fungicides (vinclozolin) and phthalates and the formation of hypospadias. An aesthetic and/or functional deficit are indications for surgical correction. The indications and the complications of hypospadias surgery must be in detail and realistically discussed with the parents and patients. Recent publications demonstrated that the risk of complications increases with the increase of the follow-up time. High-volume centers with extensive experience have a positive effect on the complication rate. Competent follow-up to adult age should be ensured.